2013
DOI: 10.1002/pon.3321
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of parent proxy report and child self‐report of posttraumatic stress in children with cancer and healthy children: influence of parental posttraumatic stress

Abstract: Objective This study examined the relationships between parental posttraumatic stress symptoms (PTSS), child PTSS, and parent-child concordance for child PTSS. Method Participants were children with cancer (n = 199) and healthy children (n = 108) and their parents. Children self-reported on PTSS and parents completed measures of child and parent PTSS. Results In the cancer group, child and parent report of child PTSS were significantly correlated with no mean differences between reporters. In contrast, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
3
23
4
Order By: Relevance
“…Interestingly, caregivers’ own PTSS were not related to child PTSS. Though this finding appears surprising, previous research has found caregiver's reports of their child's PTSS was not related to their own PTSS in a population of older youth with cancer …”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, caregivers’ own PTSS were not related to child PTSS. Though this finding appears surprising, previous research has found caregiver's reports of their child's PTSS was not related to their own PTSS in a population of older youth with cancer …”
Section: Discussioncontrasting
confidence: 71%
“…Though this remains a concern for this study and research on children <8 years of age more broadly, it is important to note that previous research found consistency between caregiver reports of child's distress and youth's reports of their own distress among pediatric cancer patients. 36…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…Data reflecting elevations in distress are based primarily on self‐report questionnaires compared to either measure norms or control groups comprised of parents of healthy children or parents of children with other acute or chronic conditions . Data from these studies indicate that a subset of PCC is at risk for marked or prolonged distress or psychopathology.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has focused on the relationship between food security status and self-reported stress. Given the children’s young age, they may not be able to reliably report their own stress, and proxy-reported stress is not reliable or valid (Clawson, Jurbergs, Lindwall, & Phipps, 2013).…”
mentioning
confidence: 99%